COGNITIVE TEST ANXIETY SCALE (CTAS): Additional evidence of validity based on university students - Feitosa Ferreira, Matheus (2025)
The main objective of this study was to gather complementary evidence on the Cognitive Test Anxiety Scale (CTAS) with university students from the Piauí coast. To this end, a study was carried out with a non-probabilistic sample (for accidental convenience) of 241 students from public (51.9%) and private (48.1%) universities in the city of Parnaíba, in the state of Piauí (Midade = 21.82; DP = 6.21; aged 18 to 65). The majority were women (74.3%), self-declared black (54.4%), single (85.1%) and studying Psychology (88.6%). They answered the CTAS, the Rosenberg Self-Esteem Scale, the Patient Health Questionnaire - 9 and a questionnaire with sociodemographic questions. The Confirmatory Factor Analysis (CFA) gathered evidence on the internal structure of the CTAS instrument, which reinforced the single-factor theoretical structure and showed a satisfactory fit (CFI = 0.994, TLI = 0.990). The internal consistency indicators were adequate: Cronbach's alpha (?) and McDonald's Omega (?), values equal to 0.92, with Composite Reliability (CC) = 0.95. In addition, Pearson's correlations showed that the CTAS presented significant relationships (p < 0.001), being negative with self-esteem (r = -0.50) and positive with depressive symptoms (r = 0.49), suggesting evidence of validity based on external measures. Finally, the EACP showed good metric qualities for Piauí university students. It is hoped that the instrument can help professionals and those interested in the subject to verify prevalence and its possible relationships with other constructs.